Thin-film morphologies of block copolymers with nanoparticles. (9th March 2015) - Jehnichen, Dieter; Pospiech, Doris; Friedel, Peter; He, Guping; Sepe, Alessandro; Zhang, Jianqi; Papadakis, Christine M.; Taurino, Rosa; Perlich, Jan
Abstract : Diblock copolymers (BCPs) show phase separation on mesoscopic length scales and form ordered morphologies in both bulk and thin films, the latter resulting in nanostructured surfaces. Morphologies in thin films are strongly influenced by film parameters, the ratio of film thickness and bulk domain spacing. Laterally structured polymer surfaces may serve as templates for controlled assembly of nanoparticles (NPs). We investigated the BCP of poly( n -pentyl methacrylate) and poly(methyl methacrylate) which show bulk morphologies of stacked lamellae or hexagonally packed cylinders. Thin films were investigated by atomic force microscopy and grazing-incidence small-angle X-ray scattering. For film thicknesses f well below d bulk, standing cylinder morphologies were observed in appropriate molar ratios, while film thicknesses around and larger than d bulk resulted in cylinders arranged parallel to surface. To alter and/or improve the morphology also in presence of different NPs (e.g., silica, gold), solvent vapour annealing (SVA) was applied. The BCP morphology usually remains unchanged but periodicities change depending on type and amount of incorporated NPs. It was found that silica clusters enlarge lateral distances of cylinders, whereas Au NPs reduce it. The effect of SVA is weak. The quality of morphology is slightly improved by SVA and lateral distances remain constant or are slightly reduced.